Physicochemical Profile of Red Ginger (Zingiber officinale) SNEDDS as Potential Antidiabetic - Sumantri Abdullah, Surya; Sudewi, Sri; Antasionasti, Irma; Rezky Putri Indarwati Abdullah (Sam Ratulangi University, 2025)
This study developed a Self-Nanoemulsifying Drug Delivery System (SNEDDS) of red ginger (Zingiber officinale var. rubrum) to enhance its stability and bioavailability. 8 formulations (F1–F8) were tested with varying Tween 80 : PEG 400 ratios (Smix 4.5 mL). Formula F7 (2.8 : 1.8 mL) produced a water-clear emulsion with pH 5.20 ± 0.02 and excellent stability for 28 days. PSA results showed droplet size 20.33 ± 0.57 nm, PDI 0.430 ± 0.053, and zeta potential −19.58 ± 1.50 mV. These findings indicated that F7 is the optimum, physicochemically stable SNEDDS formulation, potentially improving solubility and oral bioavailability of red ginger’s active compounds as a phytopharmaceutical antidiabetic candidate Keywords: red ginger, SNEDDS, nanoemulsion, physicochemical stability